Micro and nanocrystalline cellulose based oral dispersible film; preparation and evaluation of in vitro/in vivo rapid release studies for donepezil - Keshireddy AnjiReddy; Subramanian Karpagam (Universidade de São Paulo, 2020)
Oral fast-dispersible film was prepared by utlizing donepezil hydrochloride (drug) and various cellulose derivatives such as hydroxypropyl methyl cellulose (hypermellose) (HPMC), microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) to treat Alzheimer's disease. NCC was synthesized by ultra-sonication method using MCC and this was converted to thinfilm formulation (NCC-F) using solvent casting technique. The interaction between the polymer and the drug was investigated by spectral analysis such as UV, FTIR, and 1H- NMR. FTIR confirmed that the compatibility of drug and polymer in ODF formulation. NCC-F has shown an average surface roughness of 77.04 nm from AFM and the average particle size of 300 nm from SEM analysis. Nano sized particle of NCC-F leads faster in vitro dissolution rate (94.53%) when compared with MCC-F and F3 formulation. Animal model (in vivo) studies of NCC-F formulation has reached peak plasma concentration (Cmax) up to 19.018 ng/mL in the span of (tmax) 4 h with greater relative bioavailability of 143.1%. These results suggested that high surface roughness with nanosized NCC-F formulation attained extended drug availability up to (t1/2) 70 h.